Integration of contemporary trends in pedagogical education into the system of socio psychological support for the professional growth of students - Мороз, І.М.; Калениченко, Р.А.; Красильник, Ю.С. (Перспективи та інновації науки, 2025)
Based on a theoretical analysis of previous studies, the article explores the key features of socio-psychological support for the professional development of future specialists during their formation in higher education institutions. Contemporary society increasingly requires creative and proactive individuals capable of effective adaptation, self-realization, and lifelong self-development. Such individuals are able to consciously shape their own professional paths, set clear goals, and take responsibility for the outcomes of their decisions and actions. Mental self-regulation integrates energetic, dynamic, social, and semantic components, forming the foundation of a person’s conscious behavior. Creativity is a defining characteristic of a self-developing individual who is able to realize their potential through personal initiative and the selection of appropriate methods. The main components of a creative personality include motivational, intellectual, emotional, and communicative aspects. Their effective development requires expanding students’ role experiences and engaging them in diverse activities that promote creative self-expression and social interaction. The system of socio-psychological support in education must shift its focus toward fostering a creative and development-oriented learning environment. Psychological training is considered an effective tool in this process, as it helps reduce uncertainty and entropy in social change and development. Humanitarian disciplines play a particularly important role by combining theoretical knowledge with practicalskills, thus forming the core of psychological training—a crucial resource for professional and educational activity. Socio-psychological support encompasses four main functions: diagnosing problems, providing information about their nature and possible solutions, consulting during decision-making and strategy development, and offering primary assistance during implementation. A person’s transition from one activity to another is a conscious process that reflects social context and the significance of their actions. The main goal of socio-psychological support in higher education is to help individuals fully realize themselves in academic and professional spheres. Its essence lies in fostering autonomy in solving personal and professional challenges. Reducing the cognitive dissonance between school-based values and the realities of future professional activity–through controlled socio-psychological support, particularly via humanitarian education—creates a foundation for students’ successful individual and psychological adaptation to professional challenges.
Інтеграція сучасних тенденцій педагогічної освіти в систему соціально-психологічного супроводу професійного зростання студентів
Keywords: socio-psychological support; students’ professional growth; socio-psychological support of the educational process; psychological support of studen; соціально-психологічний супровід; професійне зростання студентів; соціально-психологічна підтримка освітнього процесу; психологічний супровід студентів; 378.147